Flowering plants - Leutscher, Alfred; Newman, Colin (London ; New York : F. Watts, 1984)
Describes the parts of a flower, flower families, and suggests activities to illustrate seed dispersal, pollination, and plant growth.
Includes index.
School Library Journal.
Booklist.
3.7
3-6
Keywords: Plants -- Juvenile literature; Botany -- Juvenile literature; Angiosperms -- Juvenile literature; Flowers; Plants; Botany; Plants; Angiosperms; Flowers; Plants; Botany